(untitled) (Impact: Journal of Transformation, 2021)
This article is designed to investigate the religious factors that influence the evangelization of the Garre Muslims in Moyale, Ethiopia. The Garre community is one of the Ethiopian Somali peoples who live in Moyale. Now that Moyale is situated at the border of Kenya and Ethiopia, and as was stated in the topic that the community is found on the two sides of the border, this study was carried out among the Garre who live in Ethiopia. Specifically, in carrying out this task, the study sought to examine these factors’ bearing in both the Moyale Kale Heywet and Yehiwot Birhan churches found in the region. Particularly, in coming up with reliable findings, the study employs the qualitative research data collection method. The data were collected mainly through the use of interviews, after which they were transcribed and analyzed accordingly. Through the findings of this research, various religious factors that affect the evangelization of Garre Muslims were established. These were identified as a lack of training for Christians in preparation for the task, the lack of finances for sponsoring all the activities that accompany effective evangelization, a conspicuous lack of unity among the Evangelical churches in the region - a move that would have made evangelism among the target people realistic, resistance and violence towards the Christians from Muslims, and on the part of Christians a general lack of strategies for effective mission in terms of reaching out the Garre Muslims with the Gospel message. This study also uncovers the missiological implication for the Garre Muslims in the area. Finally, the findings also demonstrate the importance of contextualization in reaching out to the Garre Muslims, rendering holistic ministries. On the part of Christians, the study established that there is a need for all the evangelical Churches in the region to be intentional both individually and corporately in establishing and enhancing vibrant evangelism among the Muslims through proper training and supporting of missionaries from the individual churches in all ways. From the foregoing, it follows that, for the expected results to be realized since they go hand in hand, this factor needs to be implemented together with all the other factors that were found affecting evangelization among the Garre community.